The Comparison of Executive Functions with the Attachment Styles in Students with and without ODD - Hamid Kargar-barzi; Sepideh Shishehfar; Alireza Jafari; Elham Ghorbanian; Askar Choobdari (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objectives: One of the causes, concerns about mental health and impact on the growth and performance of children is the increased prevalence of behavioral disorders in children. Therefore, the present study aims to compare executive functions in terms of organization- programming and selective attentionprocessing speed with the attachment styles in students with and without ODD. Material and Methods: The study is of causal- comparative nature. The statistical population includes all elementary school third to sixth grader male students with and without the ODD city of Karaj in the academic year 2015-16. 40 students having the disorder were chosen by convenience method and 40 ones without the disorder were chosen by cluster method. The participants completed the Andre Ray test, d2, attachment scale in children of middle and CSI 4 test. Data analysis was carried out by a multivariate analysis of variance (MANOVA) and independent T. Results: It was revealed that organizing- planning in children with the disorder in the process of drawing of the fiure (t (78)= 4.2, P<0.001) also in the process of drawing from memory (t (78)= 4.2, P<0.001) is signifiantly lower than the ones without it. However the difference is not signifiant in selective attention- processing speed (t (78)= 81.1, P>0.05). Conclusion: Executive functions in children with oppositional defint disorder are signifiantly lower than normal children and also, insecure attachment included consequences such as oppositional behavior, poor education and lack of proper relations with others in these children. Therefore, it is proposed that therapists of the children with the disorder consider some exercises to reinforce and improve the mother- child relation as well as executive functions of these people in order to improve their social and educational functions.